The Mysidae (Crustacea, Mysida) of the ANDEEP I–III expeditions to the Antarctic deep sea with the description of twelve new species, establishment of four new genera and with world-wide keys to the species of Erythropinae and Mysidellinae - Wittmann, Karl J. (European Journal of Taxonomy, 2024)
Twenty-one species of Mysidae were sampled by three ANDEEP expeditions to the Southern Ocean with epibenthic sledges dragged over the deep-sea floor in the realm of 58–71° S and 00–65° W, depth 774–5190 m. Previously known ranges are significantly extended southward for four species and to greater depth in the same four species plus two other species. Supplementary descriptions are given for Amblyops tattersalli and Dactylamblyops murrayi, and a first description of a (subadult) male for Thalassomysis tattersalli. The definitions of the genera Amphiakrops gen. nov., Chelamblyops gen. nov., Desmocornea gen. nov. and Schizurakrops gen. nov. are mainly based on the structure of the eyes as well as of the antennal peduncle, chelate second thoracic endopod and telson. These structures are also important for the descriptions of Amblyops arianii sp. nov., A. bipapillatus sp. nov., Amblyopsoides fenestragothica sp. nov., A. lepidophthalma sp. nov., Amphiakrops brandtae gen. et sp. nov., Dactylamblyops benthophilus sp. nov., Desmocornea subchelata gen. et sp. nov., Paramblyops petrescui sp. nov., Schizurakrops meesi gen. et sp. nov., Scolamblyops muehlenhardtae sp. nov., Stellamblyops doryphorus sp. nov. and Mysidella antarctica sp. nov. Six previously described taxa are recombined as Amblyopsoides laticauda comb. nov., Amphiakrops bidigitatus comb. nov., A. japonicus comb. nov., Chelamblyops globorostris comb. nov., Meierythrops tattersalli comb. nov. and M. triangulatus comb. nov. One species is revised back to the initial combination as Dactylamblyops japonicus. All except one (Mysidella antarctica sp. nov.) newly described (12), newly recombined (6) or back-combined (1) species belong to the Erythropinae. Keys to the resulting 61 genera and 263 species of Erythropinae and 18 species of Mysidellinae are given at the world-wide scale. Ocular papillae with a terminal pore (sensory pore organ) are recorded in nine ANDEEP species. The organ of Bellonci is identified on the reduced eyes in 16 species, among which D. subchelata gen. et sp. nov. has many ommatidia arranged in a self-contained ribbon which shows a banded rhabdom only in non-adults. Reduction of visual elements together with shrinking of ocular papillae during ontogenetic development suggest that non-adults of D. subchelata and T. tattersalli stay in the photic zone for feeding and growth and then descend only once during their lifetime to the abyss for reproduction.